Recrystallization in Materials Processing - Glebovsky, Vadim (IntechOpen, 2015)
The book Recrystallization in Materials Processing shows selected results obtained during the last few years by researchers worked on recrystallization-related issues. These researchers offer their knowledge from a range of scientific disciplines, such as materials science, metallurgy and pharmacology. The authors emphasize that the progress in this particular field of scientific research is possible today due to coordinated efforts of many research groups that work in materials science, chemistry, physics, pharmacology, and other sciences. Thus, it is possible to perform a detailed analysis of the scientific problem. The analysis starts from the selection of appropriate techniques and methods of characterization. It is then combined with the development of new tools in diagnostics, and it finished with physical modeling of phenomena.